A time-frequency analysis of sovereign debt contagion in europe - Ojo,Mustapha Olalekan (2019)
This paper adopted a wavelet approach to investigate the financial contagion in the Eurozone debt market during various crisis-ridden periods in the zone. We used weekly 10-year bond yield data and showed that until the onset of the financial crisis of 2007/2008, bond yields were highly synchronised among all countries. However, the bond yields in Greece, Ireland, Italy, Spain, and Portugal became unsynchronised with core countries after 2008. Similarly, there was no synchronisation among the periphery countries during this period, except for Italy and Spain. We found evidence of contagion emanating from Ireland during the first part of the sovereign debt crisis until around 2010, and from Greece afterwards. We also established that contagion spread to Portugal, Greece and Ireland, and can be observed at high frequencies. However, Italy and Spain were not affected. At business cycle frequencies, we found that the Greek crisis propelled a flight-to-quality flow to Belgium, Finland, France and Germany.